Intersexual segregation in foraging microhabitat use by Magellanic Woodpeckers (Campephilus magellanicus): Seasonal and habitat effects at the world's southernmost forests - Duron, Quiterie; Jimenez, Jaime E.; Vergara, Pablo M.; Soto, Gerardo E.; Lizama, Marlene; Rozzi Marin, Ricardo Roberto (My University, 2018)
Animals facing seasonal food shortage and habitat degradation may adjust their foraging behaviour to reduce intraspecific competition. In the harsh environment of the world's southernmost forests in the Magellanic sub-Antarctic ecoregion in Chile, we studied intersexual foraging differences in the largest South American woodpecker species, the Magellanic Woodpecker (Campephilus magellanicus). We assessed whether niche overlap between males and females decrease when food resources are less abundant or accessible, that is, during winter and in secondary forests, compared to summer and in old-growth forests, respectively. We analysed 421 foraging microhabitat observations from six males and six females during 2011 and 2012. As predicted, the amount of niche overlap between males and females decreased during winter, when provisioning is more difficult. During winter, males and females (i) used trees with different diameter at breast height (DBH); (ii) fed in trunk sections with different diameters; and (iii) fed at different heights on tree trunks or branches. Vertical niche partitioning between sexes was found in both old-growth and secondary forests. Such a niche partitioning during winter may be a seasonal strategy to avoid competition between sexes when prey resources are less abundant or accessible. Our results suggest that the conservation of this forest specialist, dimorphic and charismatic woodpecker species requires considering differences in habitat use between males and females.
Keywords: campephilus magellanicus; foraging strategy; intersexual niche overlap; resource partitioning; sub-antarctic forests